Collaborative Governance in Aceh's Mining Management: Towards Justice and Sustainability - Nurliana, Nurliana; Zulfikar, Teuku Muhammad; Ahmad, Rivai; Akhyar, Akhyar; Zamzami, Zamzami (Jurnal Administrasi Pemerintahan Desa, 2026)
The wealth of natural resources is often not directly proportional to the welfare of the community, triggering social and environmental conflicts and showing signs of the resource curse phenomenon due to weak governance. The prevalence of unlicensed mining activities has caused serious environmental damage, land degradation, and social conflict. This study aims to analyse how the Collaborative Governance framework can be implemented in Aceh to optimise the potential of the Qanun, while overcoming existing structural and institutional challenges. This study uses a descriptive qualitative research method, focusing on Collaborative Governance in Aceh's Mining Management. Data collection techniques include observation, interviews, and documentation, which are essential for gathering rich contextual information on the research topic. The results of research on mining governance in Aceh through the Qanun framework have provided a strong normative foundation, particularly in terms of distributive and procedural justice, the right to sue, and the role of the Wali Nanggroe Aceh. The implementation of collaborative governance is in its emerging phase and is not yet optimal. The main obstacles lie in the initial conditions, which are characterised by power asymmetry and resource disparities, inconsistent institutional design, and collaborative processes that fail to address crucial issues such as unlicensed mining. The failure of conventional governance requires a hybrid governance solution that legalises the informal sector on the condition of environmental and social compliance.